The Impact of the Nicaragua Case on Matters of Evidence and Fact-Finding - REICHLER, PAUL S. (Leiden journal of international law, 2012)
The Nicaragua case demonstrates the Court's competence in receiving and interpreting evidence, and in making reasoned findings of fact, even in the most complicated evidentiary context, as is often presented in cases involving use of force and armed conflict. The Court applied well-established standards for evaluating the conflicting evidence presented to it. In particular, the Court determined that greater weight should be given to statements against interest made by high-level government officials than to a state's self-serving declarations. The Court also determined that statements by disinterested witnesses with first-hand knowledge should receive greater weight than mere statements of opinion or press reports. In applying these guidelines, the Court found, correctly, that (i) the United States had used military and paramilitary force against Nicaragua both directly and indirectly, by organizing, financing, arming, and training the Contra guerrillas to attack Nicaragua; (ii) the evidence did not support a finding that the United States exercised direct control over the Contras’ day-to-day operations; and (iii) there was no evidence that Nicaragua supplied arms to guerrillas fighting against the government of El Salvador during the relevant period, or carried out an armed attack against that state. While Judge Schwebel's dissent criticized the last of these findings, in fact, the evidence fully supported the Court's conclusion. In subsequent decisions during the past 25 years, the Court has continued to rely on the approach to evidence first elaborated in the Nicaragua case and has continued to demonstrate its competence as a finder of fact, including in cases involving armed conflict (Bosnia Genocide) and complex scientific and technical issues (Pulp Mills).